Longitudinal analysis of acute and convalescent B cell responses in a human primary dengue serotype 2 infection model - Nivarthi, Usha K.; Tu, Huy A.; Delacruz, Matthew J.; Swanstrom, Jesica; Patel, Bhumi; Durbin, Anna P.; Whitehead, Stephen S.; Pierce, Kristen K.; Kirkpatrick, Beth D.; Baric, Ralph S.; Nguyen, Ngan; Emerling, Daniel E.; et al. (EBioMedicine, 2019)
Acute viral infections induce a rapid and transient increase in antibody-secreting plasmablasts. At convalescence, memory B cells (MBC) and long-lived plasma cells (LLPC) are responsible for long-term humoral immunity. Following an acute viral infection, the specific properties and relationships between antibodies produced by these B cell compartments are poorly understood. We utilized a controlled human challenge model of primary dengue virus serotype 2 (DENV2) infection to study acute and convalescent B-cell responses. The level of DENV2 replication was correlated with the magnitude of the plasmablast response. Functional analysis of plasmablast-derived monoclonal antibodies showed that the DENV2-specific response was dominated by cells producing DENV2 serotype-specific antibodies. DENV2-neutralizing antibodies targeted quaternary structure epitopes centered on domain III of the viral envelope protein (EDIII). Functional analysis of MBC and serum antibodies from the same subjects six months post-challenge revealed maintenance of the serotype-specific response in both compartments. The serum response mainly targeted DENV2 serotype-specific epitopes on EDIII. Our data suggest overall functional alignment of DENV2-specific responses from the plasmablast, through the MBC and LLPC compartments following primary DENV2 inflection. These results provide enhanced resolution of the temporal and specificity of the B cell compartment in viral infection and serve as framework for evaluation of B cell responses in challenge models. This study was supported by the Bill and Melinda Gates Foundation and the National Institutes of Health. •rDEN2Δ30 virus induced plasmablasts two weeks after infection of flavivirus-naïve human subjects.•Expanded plasmablast lineages produced type-specific antibodies including neutralizers to quaternary E protein epitopes•rDEN2Δ30-induced memory B cells retained functional, but not clonal type-specific overlap with the plasmablast response•DENV2-specific antibodies present during convalescence after rDEN2Δ30 infection are highly type-specific.•The rDEN2Δ30 challenge model is a framework against which to evaluate B cell responses to dengue natural infection and vaccination.